Peran Masyarakat dalam Pelestarian Sungai di Desa Mangunang Kecamatan Haruyan Kabupaten Hulu Sungai Tengah - Nazmatus Shalihah (Jurnal Pendidikan Kewarganegaraan, 2015)
Human life can not be separated from the environment both natural environment and social environment. The government does not pay attention to the benefits of a small river in life, then it is deemed necessary for the preservation of the river make arrangements. This study aims to determine the stream function Mangunang to people's lives in the village Mangunang Haruyan District of Hulu Sungai Tengah and the role of communities in the conservation of the river in the village Mangunang Haruyan District of Hulu Sungai Tengah.The method used in this study is a qualitative method. Source of data extracted using purposive sampling technique, which determines the subject or object to the purpose of research. Data was collected through direct observation, interviews, documentation. Data analysis techniques used namely through three stages namely data reduction, data presentation, draw conclusions.The results of this study indicate that the stream function for the life of the village community Mangunang has undergone a change or a decrease in the local community and the role performed villagers Mangunang to the preservation of the river is very alarming. Which caused a decline in water quality is due to the lack of awareness and concern for the environment, especially the river.Based on the research results, it can be suggested that the public is more concerned about the environment by creating a program that is coordinated by village officials example by cleaning up the river every 6 (six) months and to local governments in order to conduct a briefing form of counseling so that people do not throw garbage into the river and also semabrangan dredging the river so shallow that the river no longer be swift river currents.